Design and characteristic analysis of magnetostrictive bistable vibration harvester with displacement amplification mechanism. (1st September 2021) - Liu, Huifang; Zhao, Luyao; Chang, Yunlong; Cong, Chen
Highlights: The introduction of the bistable structure improves frequency characteristics. Displacement amplification mechanism is added to improve harvesting capability. The most suitable distance of repulsive permanent magnets is 8 mm. The most optimal stiffness ratio is determined to be 1.852. Abstract: The working frequency of a traditional cantilever magnetostrictive vibration harvester is often higher than ambient vibration frequency. In order to make it better applied to the actual ambient vibration and improving its harvesting capacity, a bistable Fe-Ga alloy vibration harvester with displacement amplification mechanism is systematically studied in this paper. On the one hand, a bistable structure is designed based on its two unique restoring force potential wells. On the other hand, a displacement amplification mechanism is added. Utilizing magnetic dipole model theory, harmonic balance theory, etc., a nonlinear lumped-parameter coupled model of the entire system is established. Moreover, the output characteristics of the system are simulated and experimentally tested. Simulation results show that when the distance of repulsive permanent magnets is 8 mm, bistable phenomenon is the most obvious. When the stiffness ratio is 1.852, the entire system has better output characteristics. Experimental results show that when excitation level is 6.272 m/s 2, the first-order resonance frequency is reduced from 60 Hz to 22 Hz, and the peak voltage is increased from 51 mV to 510 mV. In addition, two lower second-order and third-order resonance frequencies appear, which are respectively 28 Hz and 34 Hz. Currently, the voltages are also larger, reaching 590 mV and 550 mV. It is concluded that the bistable vibration harvesting system with displacement amplification mechanism can work well in the low and wide frequency region and greatly increase the voltage. Compared with a traditional cantilever magnetostrictive vibration harvester, it has better dynamic response.